INVENTARISASI DAN SEBARAN LAHAN KRITIS DI KABUPATEN SITUBONDO - Aryo Fajar Sunartomo (University of Jember, 2011)
Critical land is land that is currently unproductive due to the management and use of land which is not or less attention to soil and water conservation requirements. It thus affects the occurrence of erosion, damage to physical, chemical, water system and its environment. This study is to identify critical land in the district and its spread through spatial modeling Situbondo with reference to the criteria and standards for the determination of critical land and instrument data processing with GIS support. The research method used in this study is a description of research methods. This method aims to make remote sensing, systematic, factual, and accurate information regarding the facts and the nature of a particular population or area. Results overlay each of the criteria that determine the critical level of the land, the district has a land area that is critical to the major categories in Arjasa, Asembagus and Banyuputih with a total area of the 3 (three) districts reached 74.414 ha. Of 4 (four) categories of land that are critical in Situbondo, land with potentially critical category has the largest area of all districts with a total area of 54.95 ha or 36% of the total land.Key words : Critical land, conservation of soil and water, remote sensing systematic